The economic role of small ruminants in agricultural communities and land use systems in Africa - Kaufmann, Ralph R. von; Wilson, R.T.; Reynolds, L. (Technical Centre for Agricultural and Rural Cooperation, 1986)
Outlines the economic role of sheep and goats in the food production systems of rural communities in Africa, analysing constraints limiting their contribution to the welfare of small farm/low income producers and prescribing methods for overcoming them.